Community structures of N-2-fixing bacteria associated with the phyllosphere of a Holm oak forest and their response to drought - Rico, L; Ogaya, R; Terradas, J; Penuelas, J (PLANT BIOLOGY, 2014)
Biological nitrogen (N) fixation is a key pathway in terrestrial ecosystems and is therefore critical for understanding the responses of ecosystems to global environmental changes. The free-living diazotrophic community is distributed along the canopy-to-soil profile, but the ecological significance of epiphyllic N-2 fixers, despite their functional relevance, on plant foliar surfaces remains very poorly understood compared with the N-2-fixing community in forest litter and soils. We assessed the community structure of N-2 fixers and overall bacteria by genetic fingerprinting (t-RFLP) to explore the seasonal successional patterns of the microbial community in the natural phyllosphere of a Holm oak (Quercus ilex) forest submitted to 12-year field experiment of rain exclusion mimicking the conditions of drought projected for the coming decades. Leaves of Holm oak were analysed in different seasons over a period of 1.5years. The bacterial community of the phyllosphere did not correspond to the surrounding soil biome in the same area. These analyses provided field evidence for the presence of free-living diazotrophs associated with the tissues of leaves of Holm oak, the dominant tree species of many Mediterranean forests. The results also revealed that the community composition is affected seasonally and inter-annually by the environment, and that the composition shifts in response to climate change. Drought treatment increased the richness of the epiphyllic microbial community, especially during the summer. These changes were associated with higher C:N ratios of leaves observed in response to drought in semiarid areas. This epiphyllic microbiota that can potentially fix N-2 extends the capacity of plants to adapt to the environment.
Keywords: Bacterial TRF richness; diazotrophic community; Drought; foliar phyllosphere; Quercus ilex; t-RFLP; Trees

Life-cycle assessment of typical Portuguese cork oak woodlands. - González-García, Sara; Dias, Ana Cláudia; Arroja, Luis (The Science of the total environment, 2013)
Cork forest systems are responsible for making an important economic contribution to the Mediterranean region, especially Portugal where the cork oak woodlands or montados contain about 32% of the world's area. The environmental profile derived from reproduction cork production and extraction in two Portuguese regions (Tagus valley and Alentejo) representative of the Portuguese sector were assessed in detail using the Life-Cycle Assessment (LCA) methodology from a cradle-to-gate perspective. The production line was divided into four stages considering all the processes involved: stand establishment, stand management, cork stripping and field recovery. According to the environmental results, there were remarkable differences between the two production scenarios mainly due to the intensity and repetition of forest activities even though the cork yield was reported to be the same. The management system in the Alentejo region presented the worse environmental profile in almost all the impact categories under assessment, mainly due to the shorter cycle duration of the mechanical cleaning and pruning processes. Cork stripping was identified in both scenarios as the production stage with the highest contribution to the environmental profile due to the cleaning and pruning processes. A sensitivity assessment concerning the cork yield was performed since the average production yields in the Portuguese montados are lower than the ones used in this study. Thus, if the cork yield is reduced, the environmental profile in both scenarios gets worse since almost all the forest activities involved are the same.
Keywords: Environment; Environmental impact; Forestry; Forestry: methods; montado; Portugal; Quercus; Quercus suber L.; Reproduction cork; Trees

Economic vulnerability of timber resources to forest fires. - Rodríguez y Silva, Francisco; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera; y Silva, Francisco Rodríguez; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera (Journal of environmental management, 2012)
The temporal-spatial planning of activities for a territorial fire management program requires knowing the value of forest ecosystems. In this paper we extend to and apply the economic valuation principle to the concept of economic vulnerability and present a methodology for the economic valuation of the forest production ecosystems. The forest vulnerability is analyzed from criteria intrinsically associated to the forest characterization, and to the potential behavior of surface fires. Integrating a mapping process of fire potential and analytical valuation algorithms facilitates the implementation of fire prevention planning. The availability of cartography of economic vulnerability of the forest ecosystems is fundamental for budget optimization, and to help in the decision making process.
Keywords: Conservation of Natural Resources; Conservation of Natural Resources: economics; Decision Making; Economic valuation; Ecosystem; Fire economic losses; Fire prevention planning; Fires; Timber valuation; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. - Limousin, Jean-Marc; Rambal, Serge; OURCIVAL, JEAN-MARC; Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; Rodríguez-Cortina, Raquel; Misson, Laurent; Joffre, Richard (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896
Keywords: allometry; Dehydration; Droughts; France; leaf area; leaf demography; litterfall; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: physiology; Plant Shoots; Plant Shoots: growth & development; Quercus; Quercus: physiology; shoot growth; Trees

Recurrent fires and environment shape the vegetation in Quercus suber L. woodlands and maquis. - Schaffhauser, Alice; Curt, Thomas; Véla, Errol; Tatoni, Thierry (Comptes rendus biologies, 2012)
The effects of fire recurrence on vegetation patterns in Quercus suber L. and Erica-Cistus communities in Mediterranean fire-prone ecosystems of south-eastern France were examined on stands belonging to 5 fire classes, corresponding to different numbers of fires (from 0 to 4) and time intervals between fires since 1959. A common pool of species was identified among the plots, which was typical of both open and closed maquis. Fire recurrence reduced the abundance of trees and herbs, whereas it increased the abundance of small shrubs. Richness differed significantly between the most contrasting classes of fire recurrence, with maximal values found in control plots and minimal values in plots that had burned recurrently and recently. Equitability indices did not vary significantly, in contrast to Shannon's diversity index which mostly correlated with richness. Forest ecosystems that have burnt once or twice in the last 50 years were resilient; that is to say they recovered a biomass and composition similar to that of the pre-fire state. However, after more than 3-4 fires, shrubland communities displayed lower species richness and diversity indices than unburned plots. The time since the last fire and the number of fires were the most explanatory fire variables, governing the structure of post-fire plant communities. However, environmental factors, such as slope or exposure, also made a significant contribution. Higher rates of fire recurrence can affect the persistence or expansion of shrublands in the future, as observed in other Mediterranean areas.
The following values have no corresponding Zotero field: accession-num: 22721564
Keywords: Acidic soil; biomass; climate; cork-oak; Ecosystem; Erica arborea L.; Fire recurrence; Fires; France; Mediterranean Region; Plant communities; Plants; Plants: classification; Quercus; Seasons; Species Specificity; Trees

Summer season and long-term drought increase the richness of bacteria and fungi in the foliar phyllosphere of Quercus ilex in a mixed Mediterranean forest - Penuelas, J; Rico, L; Ogaya, R; Jump, A S; Terradas, J (Plant Biology, 2012)
We explored the changes in richness, diversity and evenness of epiphytic (on the leaf surface) and endophytic (within leaf tissues) bacteria and fungi in the foliar phyllosphere of Quercus ilex, the dominant tree species of Mediterranean forests. Bacteria and fungi were assessed during ontogenic development of the leaves, from the wet spring to the dry summer season in control plots and in plots subjected to drought conditions mimicking those projected for future decades. Our aim was to monitor succession in microbiota during the colonisation of plant leaves and its response to climate change. Ontogeny and seasonality exerted a strong influence on richness and diversity of the microbial phyllosphere community, which decreased in summer in the whole leaf and increased in summer in the epiphytic phyllosphere. Drought precluded the decrease in whole leaf phyllosphere diversity and increased the rise in the epiphytic phyllosphere. Both whole leaf bacterial and fungal richness decreased with the decrease in physiological activity and productivity of the summer season in control trees. As expected, the richness of epiphytic bacteria and fungi increased in summer after increasing time of colonisation. Under summer dry conditions, there was a positive relationship between TRF (terminal restriction fragments) richness and drought, both for whole leaf and epiphytic phyllosphere, and especially for fungal communities. These results demonstrate that changes in climate are likely to significantly alter microbial abundance and composition of the phyllosphere. Given the diverse functions and large number of phyllospheric microbes, the potential functional implications of such community shifts warrant exploration.
Keywords: Bacteria; Bacteria: genetics; Bacteria: growth & development; Bacterial; Bacterial TRF richness; Bacterial: genetics; Biodiversity; colonisation time; DNA; Drought; Droughts; endophytes; epiphytes; foliar and epiphytic microbial diversity; foliar phyllosphere; Fungal; fungal TRF richness; Fungal: genetics; fungi; Fungi: genetics; Fungi: growth & development; Mediterranean Region; Plant Leaves; Plant Leaves: microbiology; Polymorphism; Quercus; Quercus: microbiology; Restriction Fragment Length; Seasonality; Seasons; Trees; Trees: microbiology

Modelling the influence of peri-urban trees in the air quality of Madrid region (Spain). - Alonso, Rocío; Vivanco, Marta G; González-Fernández, Ignacio; Bermejo, Victoria; Palomino, Inmaculada; Garrido, Juan Luis; Elvira, Susana; Salvador, Pedro; Artíñano, Begoña (Environmental pollution (Barking, Essex : 1987), 2011)
Tropospheric ozone (O(3)) is considered one of the most important air pollutants affecting human health. The role of peri-urban vegetation in modifying O(3) concentrations has been analyzed in the Madrid region (Spain) using the V200603par-rc1 version of the CHIMERE air quality model. The 3.7 version of the MM5 meteorological model was used to provide meteorological input data to the CHIMERE. The emissions were derived from the EMEP database for 2003. Land use data and the stomatal conductance model included in CHIMERE were modified according to the latest information available for the study area. Two cases were considered for the period April-September 2003: (1) actual land use and (2) a fictitious scenario where El Pardo peri-urban forest was converted to bare-soil. The results show that El Pardo forest constitutes a sink of O(3) since removing this green area increased O(3) levels over the modified area and over down-wind surrounding areas.
Keywords: Air Pollutants; Air Pollutants: analysis; Air Pollutants: metabolism; air pollution; Air pollution removal; Air Pollution: statistics & numerical data; Air quality models; Chemical; Cities; Dry deposition; Environmental Monitoring; Environmental Monitoring: methods; Models; Ozone; Ozone: analysis; Ozone: metabolism; Spain; Trees; Trees: classification; Trees: metabolism; Trees: physiology; Urban forest

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Plasticity and stress tolerance override local adaptation in the responses of Mediterranean holm oak seedlings to drought and cold - Gimeno, Teresa E; Pías, Beatriz; Lemos-Filho, José P; Valladares, Fernando (Tree Physiology, 2009)
Plant populations of widely distributed species experience a broad range of environmental conditions that can be faced by phenotypic plasticity or ecotypic differentiation and local adaptation. The strategy chosen will determine a population’s ability to respond to climate change. To explore this, we grew Quercus ilex (L.) seedlings from acorns collected at six selected populations from climatically contrasting localities and evaluated their response to drought and late season cold events. Maximum photosynthetic rate (Amax), instantaneous water use efficiency (iWUE), and thermal tolerance to freeze and heat (estimated from chlorophyll fluorescence versus temperature curves) were measured in 5-month-old seedlings in control (no stress), drought (water-stressed), and cold (low suboptimal temperature) conditions. The observed responses were similar for the six populations: drought decreased Amax and increased iWUE, and cold reduced Amax and iWUE. All the seedlings maintained photosynthetic activity under adverse conditions (drought and cold), and rapidly increased their iWUE by closing stomata when exposed to drought. Heat and freeze tolerances were similarly high for seedlings from all the populations, and they were significantly increased by drought and cold, respectively; and were positively related to each other. Differences in seedling performance across populations were primarily induced by maternal effects mediated by seed size and to a lesser extent by idiosyncratic physiologic responses to drought and low temperatures. Tolerance to multiple stresses together with the capacity to physiologically acclimate to heat waves and cold snaps may allow Q. ilex to cope with the increasingly stressful conditions imposed by climate change. Lack of evidence of physiologic seedling adaptation to local climate may reflect opposing selection pressures to complex, multidimensional environmental conditions operating within the distribution range of this species.
10.1093/treephys/tpn007
Keywords: Adaptation; Biological; Biological: physiology; Cold Temperature; Droughts; eﬃciency; Freezing; Genetic Variation; Hot Temperature; Nuts; photosynthesis; Photosynthesis: physiology; Physiological; Quercus; Quercus ilex; Quercus: physiology; Stress; thermal tolerance; Trees; water; water use; Water: physiology

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G; Galotta, G; Cancellieri, L; Savo, V (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

Tree roots and damages in the Jewish catacombs of Villa Torlonia (Roma) - Caneva, G.; Galotta, G.; Cancellieri, L.; Savo, V. (Journal of Cultural Heritage, 2009)
Damages to hypogeal archaeological monuments, caused by the growth of tree roots, are frequently reported in the city of Rome. Problems of compatibility between trees and underground structures may become complex in the case of historical gardens. The Jewish catacombs of Villa Torlonia show relevant conservation problems, some of them arising from damages due to root growth, and consolidating interventions seem to be urgent. Some species in the gardens, especially Ficus carica L., but also Quercus ilex L. and Pinus pinea L., have developed a strong root system, growing for many meters in lateral distance and for some meters vertically. The plants responsible for the various alterations were identiﬁed by their wood anatomy and a methodology to treat similar problems has been proposed. Data collected aim to avoid errors made in managing the plant cover of an archaeological site.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: archaeological site; catacombs; hypogeal conservation; rome; tree roots and buildings; Trees; wood anatomy

The influence of linear elements on plant species diversity of Mediterranean rural landscapes: assessment of different indices and statistical approaches. - García del Barrio, J M; Ortega, M; Vázquez De la Cueva, A; Elena-Rosselló, R (Environmental monitoring and assessment, 2006)
This paper mainly aims to study the linear element influence on the estimation of vascular plant species diversity in five Mediterranean landscapes modeled as land cover patch mosaics. These landscapes have several core habitats and a different set of linear elements--habitat edges or ecotones, roads or railways, rivers, streams and hedgerows on farm land--whose plant composition were examined. Secondly, it aims to check plant diversity estimation in Mediterranean landscapes using parametric and non-parametric procedures, with two indices: Species richness and Shannon index. Land cover types and landscape linear elements were identified from aerial photographs. Their spatial information was processed using GIS techniques. Field plots were selected using a stratified sampling design according to relieve and tree density of each habitat type. A 50x20 m2 multi-scale sampling plot was designed for the core habitats and across the main landscape linear elements. Richness and diversity of plant species were estimated by comparing the observed field data to ICE (Incidence-based Coverage Estimator) and ACE (Abundance-based Coverage Estimator) non-parametric estimators. The species density, percentage of unique species, and alpha diversity per plot were significantly higher (p < 0.05) in linear elements than in core habitats. ICE estimate of number of species was 32% higher than of ACE estimate, which did not differ significantly from the observed values. Accumulated species richness in core habitats together with linear elements, were significantly higher than those recorded only in the core habitats in all the landscapes. Conversely, Shannon diversity index did not show significant differences.
Keywords: Biodiversity; Conservation of Natural Resources; Conservation of Natural Resources: statistics & nu; core habitat; diversity; Ecosystem; ecotones; Environmental Monitoring; Environmental Monitoring: methods; Geography; landscape; linear elements; Mediterranean; Mediterranean Region; Plant Development; Poaceae; Poaceae: growth & development; Shannon index; Species richness; Species Specificity; Trees; Trees: growth & development

Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara (Biomacromolecules, 2006)
Cork suberin was partially depolymerized by methanolysis catalyzed by calcium hydroxide. Analysis by GC-MS of the methanolysate showed suberin monomers, including glycerol and long-chain α,?-diacids and ?-hydroxyacids. ESI-MS analysis of the methanolysate showed, besides the aliphatic monomers, suberin oligomers, including linear dimeric esters of α,?-diacids and ?-hydroxyacids. Two types of dimeric esters were identified:? a α,?-diacid linked to a ?-hydroxyacid and two inter-linked ?-hydroxyacids. The α,?-diacids and ?-hydroxyacids found as monomer residues in the dimeric esters were mainly the C18 monomers with midchain substituents. The identification of these dimeric esters was based in their CID-MS/MS spectra and confirmed after synthesis of model compounds. The occurrence of inter-esterified long-chain monomers in suberin brings a new insight in the understanding of the polyester structure of this biopolymer.
From Duplicate 1 (Linear Aliphatic Dimeric Esters from Cork Suberin - Graça, José; Santos, Sara)
Keywords: cork suberin; dimeric esters; Dimerization; Electrospray Ionization; Electrospray Ionization: metho; Esters; Esters: chemistry; GC-MS (voyant); Lipids; Mass; Membrane Lipids; Membrane Lipids: chemistry; Molecular Structure; Sensitivity and Specificity; Spectrometry; Trees; Trees: chemistry

Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L (Tree Physiology, 2004)
Photoinhibition was examined in four co-occurring Mediterranean evergreen tree species during two consecutive winters. In response to low temperatures and saturating light, Juniperus phoenicea L., Pinus halepensis Mill., Quercus coccifera L. and Q. ilex ssp. ballota (Desf.) Samp. exhibited marked chronic photoinhibition, indicated by low predawn maximal photochemical efficiency of photosystem II (PSII) (Fv/Fm). Low Fv/Fm values were correlated with high concentrations of xanthophyll cycle components (VAZ) and with the maintenance of high concentrations of zeaxanthin overnight (DPSpd). In all species, however, chronic photoinhibition was enhanced as the winter progressed in the absence of changes in DPSpd, suggesting cumulative damage toward the end of winter.Photoinhibition differed among species: P. halepensis always displayed significantly higher Fv/Fm values; and Q. coccifera had the lowest Fv/Fm values, showing a high sensitivity to the combination of high light and low temperatures. Differences among species were not fully explained by differences in the xanthophyll pool or its de-epoxidation state. Chronic photoinhibition overlapped with a dynamic photoinhibition as shown by the low values of photochemical efficiency of the open reaction centers of PSII at midday. Winter photoprotective strategies differed among species and may involve photoprotective mechanisms in addition to those associated with xanthophylls. The observed species-specific differences matched results obtained for the same species in summer; however, comparison of the two seasons suggests that the higher VAZ concentration observed in winter has an additional structural photoprotective role.
From Duplicate 2 (Winter photoinhibition in the field involves different processes in four co-occurring Mediterranean tree species - Martínez-Ferri, E; Manrique, E; Valladares, F; Balaguer, L)
Keywords: chlorophyll; Chlorophyll: physiology; Juniperus; Juniperus: physiology; photoprotection; Pinus; Pinus: physiology; Plant Leaves; Plant Leaves: physiology; Quercus; Quercus: physiology; Seasons; Sunlight; Trees; Trees: physiology; xanthophyll cycle

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Nitrogen deposition in Mediterranean forests. - Rodà, F; Avila, a; Rodrigo, a (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Nitrogen deposition in Mediterranean forests. - Roda, F.; Avila, a; Rodrigo, A. (Environmental pollution (Barking, Essex : 1987), 2002)
Atmospheric deposition of inorganic nitrogen was studied at two forested sites in the Montseny mountains (northeast Spain), peripheral to the Barcelona conurbation, and at a nearby lowland town, using bulk deposition, wet-only deposition, throughfall, and dry deposition inferred from branch-washes and surrogate surfaces (metacrylate plates). Bulk deposition inputs of ammonium and nitrate did not show significant temporal trends over a 16-year period. Bulk inputs of inorganic N were moderate, ranging from 6 to 10 kg N ha(-1) year(-1) depending on the time period considered and the degree of site exposure to polluted air masses from the Barcelona conurbation. Large dry-sedimented particles played a minor role, since wet-only inputs were virtually identical to bulk inputs. On the contrary, branch- and plate-washes indicated substantial dry inputs of N gases and small particles. Total atmospheric deposition was estimated at 15-22 kg N ha(-1) year(-1), most of it being retained within the studied broadleaved evergreen forests. Ecosystem N availability is thus likely to be increasing in these forests.
The following values have no corresponding Zotero field: accession-num: 11939283
Keywords: Air Pollutants; Air Pollutants: analysis; Biological Availability; Ecosystem; Environmental Monitoring; Gases; Geologic Sediments; Geologic Sediments: chemistry; Mediterranean Region; nitrogen; Nitrogen: analysis; Particle Size; Trees; Trees (citation)

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N; Pemonge, M.-H. H; Ouassou, A; Sbay, H; Kremer, A; Petit, R J (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Frequent cytoplasmic exchanges between oak species that are not closely related: Quercus suber and Q. ilex in Morocco - Belahbib, N.; Pemonge, M.-H. H.; Ouassou, A.; Sbay, H.; Kremer, A.; Petit, R. J. (Molecular Ecology, 2001)
Chloroplast (cp) and mitochondrial (mt) DNA variation were studied in 97 populations of cork oak (Quercus suber) in Morocco; in 31 of these populations, holm oak (Quercus ilex), a clearly distinct species, also occurred and was compared with Q. suber. Three cpDNA and one mtDNA primer pairs were used in the survey, each in combination with one restriction enzyme. Six haplotypes belonging to two very divergent lineages were detected; one lineage predominates in each species, and is probably ancestral, as inferred from comparisons with other oak species. In the mixed-species populations, cytoplasmic genomes were frequently shared across species, as indicated by an introgression ratio of 0.63. This index is a new measure of the propensity of species to share locally genetic markers, varying from zero (complete differentiation) to one (no differentiation). By contrast, more closely related deciduous oak species (Q. robur, Q. petraea and Q. pubescens) have introgression ratios varying from 0.82 to 0.97. The introgression events appear to have been more frequent in the direction Q. ilex (female) × Q. suber (male), a finding which seems attributable to the flowering phenology of these two species. This asymmetry may have favoured immigration of Q. suber beyond its main range, in regions already colonized by Q. ilex. There, rare hybridization and further introgression through long distance pollen flow have established populations that are morphologically indistinguishable from Q. suber but that have cytoplasmic genomes originating from the local Q. ilex populations.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11555243
Keywords: Chloroplast; Chloroplast: genetics; cpDNA; DNA; Evolution; Genetic; Genetic Markers; Genetic Variation; Genetic: genetics; geographical structure; Haplotypes; Hybridization; introgression; Mitochondrial; Mitochondrial: genetics; Models; Molecular; Morocco; mtDNA; PCR–RFLP; Quercus; Quercus: genetics; Trees; Trees: genetics

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R.; Perotto, S.; Girlanda, M.; Vidano, G.; Luppi, a M. (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11050558
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R; Perotto, S; Girlanda, M; Vidano, G; Luppi, a M (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Antimutagenicity of a suberin extract from Quercus suber cork. - Krizková, L; Lopes, M H; Polónyi, J; Belicová, a; Dobias, J; Ebringer, L (Mutation research, 1999)
The possible protective effect of a suberin extract from Quercus suber cork on acridine orange (AO)-, ofloxacin- and UV radiation-induced mutagenicity (bleaching activity) in Euglena gracilis was examined. To our knowledge, the present results are the first attempt to analyse suberin in relation to mutagenicity of some chemicals. Suberin exhibits a significant dose-dependent protective effect against AO-induced mutagenicity and the concentration of 500 micrograms/ml completely eliminates the Euglena-bleaching activity of AO. The mutagenicity of ofloxacin is also significantly reduced in the presence of suberin (125, 250 and 500 micrograms/ml). However, the moderate protective effect of suberin on UV radiation-induced mutagenicity was observed only at concentrations 500 and 1000 micrograms/ml. Our data shows that suberin extract from Q. suber cork possess antimutagenic properties and can be included in the group of natural antimutagens acting in a desmutagenic manner.
Keywords: Acridine Orange; Acridine Orange: toxicity; Animals; Antimutagenic Agents; Antimutagenic Agents: pharmacology; Euglena gracilis; Euglena gracilis: drug effects; Euglena gracilis: genetics; Euglena gracilis: radiation effects; Lipids; Membrane Lipids; Membrane Lipids: pharmacology; Mutagenicity Tests; Mutagenicity Tests: methods; Mutagens; Mutagens: toxicity; Ofloxacin; Ofloxacin: toxicity; Plant Extracts; Plant Extracts: pharmacology; Plant Shoots; Plant Shoots: chemistry; Spectrophotometry, Ultraviolet; Superoxides; Superoxides: metabolism; Trees; Trees: chemistry; Ultraviolet Rays

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions - Kesselmeier, J; Bode, K; Gerlach, C; Jork, E.-M (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances
Keywords: acetic acid; assimilation; Atmosphere; crop plants; exchange of volatile organic compounds; formic acid; leaf conductance; organic acids; Plants; Transpiration; Trees

Impacts of climate change and elevated CO2 on trees in regions with a Mediterranean type of climate - Pereira, J S; Chaves, M M (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
Research on the effects of global changes on Mediterranean trees is still limited. In terms of growth response to elevated CO2, Mediterranean trees were not different from temperate-zone trees, i.e., growth enhancement seems to be short-lived, declining after the first growing seasons in elevated CO2. In Mediterranean landscapes important soil fertility gradients can be found. Such differences, mainly in soil nitrogen, may interact with elevated CO2, as shown by the enhancement of the response to high CO2 by abundant N in Fraxinus angustifolia (a deciduous, riparian tree) and Quercus suber (an evergreen oak). Given the characteristics of the regional climate, special attention in research was given to the interaction between elevated CO2 and the summer stress, i.e., heat and high irradiance stresses superimposed on water deficits. We discuss the possibility that elevated CO2 may alleviate some of the negative effects of that summer stresses, as was found in Quercus suber seedlings under controlled conditions or in Quercus ilex with a life-time exposure to elevated CO2.
Keywords: Elevated CO2; Mediterranean; Trees; water stress

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Phenological and growth patterns of the Mediterranean oak Quercus suber L. - Oliveira, Graca; Correia, Otflia (Trees-Structure and …, 1994)
The phenology of Quercus suber L., a dominant species of the montados in the Iberian Peninsula, was studied for 2 years in southwest Portugal. The seasonal progression of phenological events was analyzed in seven trees. Selected branches were examined monthly for shoot elongation, leaf number, branching, flowering, and fruiting. Radial stem growth and specific leaf weight were also studied. Active growth was observed from early spring to early summer. Reserves accumulated during winter and high photosynthetic activity in early spring apparently supported this strong development. The growth flush started with stem radial increment, which seemed to be impaired by spring rainfall. Male inflorescence production was the next phenological event. Old leaves were shed during new twig and leaf emergence. Shoot elongation and the number of new leaves produced were well correlated with the previous-year shoot's length, and were not clearly related to climatic factors. Radial growth resumed in au- tumn at a lower rate than in the previous spring, a possible consequence of a reserve depletion due to lower photo- synthetic production in summer and investment on fruit maturation, which was complete by late autumn. Premature and excessive new leaf production were apparently sub- jected to self-pruning strategies related to the development of each tree's crown. Younger cork-oaks produced shorter and fewer shoots per module, and more sclerophyllous leaves than the older ones. A high intra-specific variability was observed in all the results.
Keywords: Growth; Phenology; Quercus suber; specific leaf weight; Trees

Phenological and growth patterns of the Mediterranean oak Quercus suber L. - Oliveira, Graca; Correia, Otflia (Trees-Structure and …, 1994)
The phenology of Quercus suber L., a dominant species of the montados in the Iberian Peninsula, was studied for 2 years in southwest Portugal. The seasonal progression of phenological events was analyzed in seven trees. Selected branches were examined monthly for shoot elongation, leaf number, branching, flowering, and fruiting. Radial stem growth and specific leaf weight were also studied. Active growth was observed from early spring to early summer. Reserves accumulated during winter and high photosynthetic activity in early spring apparently supported this strong development. The growth flush started with stem radial increment, which seemed to be impaired by spring rainfall. Male inflorescence production was the next phenological event. Old leaves were shed during new twig and leaf emergence. Shoot elongation and the number of new leaves produced were well correlated with the previous-year shoot's length, and were not clearly related to climatic factors. Radial growth resumed in au- tumn at a lower rate than in the previous spring, a possible consequence of a reserve depletion due to lower photo- synthetic production in summer and investment on fruit maturation, which was complete by late autumn. Premature and excessive new leaf production were apparently sub- jected to self-pruning strategies related to the development of each tree's crown. Younger cork-oaks produced shorter and fewer shoots per module, and more sclerophyllous leaves than the older ones. A high intra-specific variability was observed in all the results.
Keywords: Growth; Phenology; Quercus suber; specific leaf weight; Trees

Photosynthetic acclimation in trees to rising atmospheric CO2: a broader perspective - Gunderson, C. A.; Wullschleger, S. D. (Photosynthesis Research, 1994)
Analysis of leaf-level photosynthetic responses of 39 tree species grown in elevated concentrations of atmospheric CO 2 indicated an average photosynthetic enhancement of 44% when measured at the growth [CO2]. When photosynthesis was measured at a common ambient [CO2], photosynthesis of plants grown at elevated [CO2] was reduced, on average, 21% relative to ambient-grown trees, but variability was high. The evidence linking photosynthetic acclimation in trees with changes at the biochemical level is examined, along with anatomical and morphological changes in trees that impact leaf- and canopy-level photosynthetic response to CO 2 enrichment. Nutrient limitations and variations in sink strength appear to influence photosynthetic acclimation, but the evidence in trees for one predominant factor controlling acclimation is lacking. Regardless of the mechanisms that underlie photosynthetic acclimation, it is doubtful that this response will be complete. A new focus on adjustments to rising [COz] at canopy, stand, and forest scales is needed to predict ecosystem response to a changing environment.
The following values have no corresponding Zotero field: accession-num: 24311130
Keywords: elevated atmospheric CO 2; global carbon cycle; photosynthetic acclimation; Trees

Photosynthetic acclimation in trees to rising atmospheric CO2: a broader perspective - Gunderson, C A; Wullschleger, S D (Photosynthesis Research, 1994)
Analysis of leaf-level photosynthetic responses of 39 tree species grown in elevated concentrations of atmospheric CO 2 indicated an average photosynthetic enhancement of 44% when measured at the growth [CO2]. When photosynthesis was measured at a common ambient [CO2], photosynthesis of plants grown at elevated [CO2] was reduced, on average, 21% relative to ambient-grown trees, but variability was high. The evidence linking photosynthetic acclimation in trees with changes at the biochemical level is examined, along with anatomical and morphological changes in trees that impact leaf- and canopy-level photosynthetic response to CO 2 enrichment. Nutrient limitations and variations in sink strength appear to influence photosynthetic acclimation, but the evidence in trees for one predominant factor controlling acclimation is lacking. Regardless of the mechanisms that underlie photosynthetic acclimation, it is doubtful that this response will be complete. A new focus on adjustments to rising [COz] at canopy, stand, and forest scales is needed to predict ecosystem response to a changing environment.
Keywords: elevated atmospheric CO 2; global carbon cycle; photosynthetic acclimation; Trees

HOW TREE COVER INFLUENCES THE WATER-BALANCE OF MEDITERRANEAN RANGELANDS - Joffre, R; Rambal, S (ECOLOGY, 1993)
Dehesa ecosystems of the southwestern Iberian Peninsula are characterized as a savanna-like rangeland dominated by scattered mediterranean evergreen oak trees. We investigated whether isolated trees modify the water balance of this ecosystem and if so, what implications this finding might have on models that assume homogeneity of soil water resources. The water balance of the two ecological components of the dehesas-(1) the tree-grass component, and (2) the open areas between the tree canopies with unshaded grass vegetation-was studied for three consecutive years in three locations in the Sierra Norte de Sevilla region of Andalusia in southern Spain. In this region, annual rainfall was generally between 600 and 800 mm, and the summer drought lasted almost-equal-to 130 d. Soil water storage was measured with a neutron moisture gauge outside and under the tree canopy. Deep drainage between two consecutive census dates was calculated using field-measured drainage characteristics. Evapotranspiration (Ea) and surface runoff were computed from the water balance equation assuming that Ea is limited by Penman potential evapotranspiration. Monthly Ea by annual species in open areas was poorly correlated with rainfall levels in the autumn and was limited during the spring by availability of water in the top 40 cm of soil. During summer, monthly Ea by trees ranged from 30 to 50 mm. Mean annual Ea was 400 mm outside and 590 mm under the tree cover. In open areas, water yield (WY), defined as the sum of deep drainage and surface runoff, ranged from 65 to 100% of total Ea, whereas under the tree canopy WY was only 20 to 40% of the Ea. Under the tree canopy, when annual precipitation was < 570 mm, WY was negligible and all precipitation was lost by evapotranspiration. Outside the tree canopy, WY occurred as soon as annual precipitation exceeded 250 mm. Models of competition between trees and grass generally assume a spatial homogeneity of soil hydrodynamic properties. Our results, however, show that both soil water storage and evapotranspiration are greater for the tree-grass component. Consequently, these models must account for this spatial variability in water resources according to species.
Keywords: DEEP DRAINAGE; Dehesa; Evapotranspiration; Grasses; hydrological equilibrium; MEDITERRANEAN OAK WOODLANDS; Quercus ilex; Quercus-suber; surface runoff; Trees; water balance